Rare Association of Bilateral Anotia with Congenital Facial Palsy - Bhatnagar, Ruchika; Prasad, Prem Lochan (Journal of Nepal Paediatric Society, 2016)
Anotia is a birth defect and is associated with facial palsy and congenital heart defect as various presentation of cardiofacial syndrome. Herein we report a case of bilateral anotia and unilateral congenital facial palsy without congenital heart disease. It may occur due to single gene abnormality, teratogenic effect of maternal ingestion of thalidomide, retinoic acid, misoprostol or maternal diabetes, dietary lack of carbohydrates and folate. J Nepal Paediatr Soc 2015;35(2):195-197